2020
DOI: 10.3390/cells9091987
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-Mediated Inhibition of CTLA4 Aggravates Atherosclerotic Plaque Inflammation and Progression in Hyperlipidemic Mice

Abstract: T cell-driven inflammation plays a critical role in the initiation and progression of atherosclerosis. The co-inhibitory protein Cytotoxic T-Lymphocyte Associated protein (CTLA) 4 is an important negative regulator of T cell activation. Here, we studied the effects of the antibody-mediated inhibition of CTLA4 on experimental atherosclerosis by treating 6–8-week-old Ldlr−/− mice, fed a 0.15% cholesterol diet for six weeks, biweekly with 200 μg of CTLA4 antibodies or isotype control for six weeks. 18F-fluorodeox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 36 publications
1
43
0
Order By: Relevance
“…Immunohistochemistry was performed for MAC3 (BD Pharmingen), alpha smooth muscle actin (Sigma-Aldrich), CD3 (AbD Serotec), CD8 (eBioscience), Ki67 (Abcam) and TUNEL ( in situ apoptosis detection kit, Roche). The stability index was defined as (% α smooth muscle actin/% necrotic core; Poels et al, 2020 ). Double immunohistochemical stainings were performed with rabbit anti-mouse PFKFB3 antibody (Abcam, AB2617178) in combination with CD31 (Dianova, Hamburg, Germany), and the previously mentioned MAC3, CD3 and alpha smooth muscle actin.…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemistry was performed for MAC3 (BD Pharmingen), alpha smooth muscle actin (Sigma-Aldrich), CD3 (AbD Serotec), CD8 (eBioscience), Ki67 (Abcam) and TUNEL ( in situ apoptosis detection kit, Roche). The stability index was defined as (% α smooth muscle actin/% necrotic core; Poels et al, 2020 ). Double immunohistochemical stainings were performed with rabbit anti-mouse PFKFB3 antibody (Abcam, AB2617178) in combination with CD31 (Dianova, Hamburg, Germany), and the previously mentioned MAC3, CD3 and alpha smooth muscle actin.…”
Section: Methodsmentioning
confidence: 99%
“…Both T cell-specific overexpression of CTLA4 or treatment with the CTLA4-Ig fusion protein Open access abatacept reduced atherosclerosis in hyperlipidemic mice, whereas antibody-mediated inhibition of CTLA4 increased atherosclerotic burden in Ldlr −/− mice. [50][51][52][53] Blockage of CTLA4 induced an activated CD4 + and CD8 + T-cell profile in the circulation and lymphoid organs and promoted activation of the aortic endothelium. 53 Atherosclerotic lesion size increased on CTLA4 inhibition and plaques contained more T cells, which promoted necrotic core formation and subsequent plaque progression towards an advanced, clinically unfavorable phenotype.…”
Section: Pathophysiology Of Ici-related Atherosclerotic Cvdmentioning
confidence: 99%
“…[50][51][52][53] Blockage of CTLA4 induced an activated CD4 + and CD8 + T-cell profile in the circulation and lymphoid organs and promoted activation of the aortic endothelium. 53 Atherosclerotic lesion size increased on CTLA4 inhibition and plaques contained more T cells, which promoted necrotic core formation and subsequent plaque progression towards an advanced, clinically unfavorable phenotype. 53 As combined inhibition of CTLA4 and PD1 is a therapeutic strategy for several malignancies, we recently investigated the effects of dual antibody-mediated inhibition of CTLA4 and PD1 on atherosclerosis in Ldlr −/− mice.…”
Section: Pathophysiology Of Ici-related Atherosclerotic Cvdmentioning
confidence: 99%
“…Several human and murine studies already demonstrated accelerated immune processes after blocking or depleting PD-1 or its ligand PD-L1, with parallel increased lesional CD4 + and CD8 + T cell levels in atherosclerosis [ 68 , 91 , 92 ]. The combined treatment of mice with immune checkpoint inhibitors targeting both PD-1 and cytotoxic T lymphocyte-associated antigen-4 (CTLA-4), or CTLA inhibition alone, increased both CD4 + effector T cell and CD8 + cytotoxic T cell numbers in the arterial wall of hyperlipidemic mice [ 93 ]. A recent clinical study furthermore demonstrated that cardiovascular events were higher after initiation of immune checkpoint inhibitor treatment, potentially mediated by accelerated progression of atherosclerosis [ 94 ].…”
Section: Cd8 + T Cells and Immunotherapymentioning
confidence: 99%